2022
DOI: 10.3390/ijerph19020629
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Perception Identification and Classification Based on Electroencephalogram (EEG) Features

Abstract: This paper puts forward a new method of landscape recognition and evaluation by using aerial video and EEG technology. In this study, seven typical landscape types (forest, wetland, grassland, desert, water, farmland, and city) were selected. Different electroencephalogram (EEG) signals were generated through different inner experiences and feelings felt by people watching video stimuli of the different landscape types. The electroencephalogram (EEG) features were extracted to obtain the mean amplitude spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The accuracy of GA-BP network is 90.8%, which is better than traditional BP network and support vector machine [33]. In 2022, Wang Yuting compared the classification results of EEG signals by back propagation (BP) neural network, K-nearest neighbour classification (KNN), Random forest (RF) and support vector machine (SVM), and concluded that the SVM had the best classification effect [34][35][36][37][38]. In 2022, Zeng Wei et al proposed a laser ultrasound detection method based on the PSO-SVM algorithm for the identification and detection of human skin tumours [39].…”
Section: Research On Physiological Signal Processing Methodsmentioning
confidence: 99%
“…The accuracy of GA-BP network is 90.8%, which is better than traditional BP network and support vector machine [33]. In 2022, Wang Yuting compared the classification results of EEG signals by back propagation (BP) neural network, K-nearest neighbour classification (KNN), Random forest (RF) and support vector machine (SVM), and concluded that the SVM had the best classification effect [34][35][36][37][38]. In 2022, Zeng Wei et al proposed a laser ultrasound detection method based on the PSO-SVM algorithm for the identification and detection of human skin tumours [39].…”
Section: Research On Physiological Signal Processing Methodsmentioning
confidence: 99%
“…Each individual decision tree generates a prediction result, and the final prediction is performed by implementing the major voting method, as shown in Figure 4 . The RF classifier has been widely utilized to classify EEG signals for evaluating the stages of sleep and diagnosing sleep problems [ 20 ] and identifying landscape perception [ 21 ] due to the good balance between execution time and reliability. Therefore, RF is employed to classify the EEG signals for the evaluation of the performance of the features extracted from the AE.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the classification performance, this study compared the experimental results of different methods: naive bayes [2], support vector machine (SVM) [27],random forest [50], deep recurrent-CNN for EEG images [51] (referred to as iDRCNN in the remainder of this manuscript), EEGNet [30], DeepConvNet [9], ShallowConvNet [9], and Conformer [18].…”
Section: Model Trainingmentioning
confidence: 99%